The Healthcare Model of the Lombardy Region (1995-2012): The transformed system - Mateos Buendía, Inmaculada (Cuadernos de Gobierno y Administración Pública, 2017)
The changes of the health system models in Europe, have reached a great relevance in the last decades. The Welfare State had to confront its own transformation, adapting to the demands of the social and economic contexts. The model of the National Health Service of the Lombardy Region experiments a transition and evolution, which show a new approach to its health policy. The reform process is centered on the decentralisation of the production and provision of the health goods and services. The introduction of market logics has favoured the externalisation of the provision of these goods and services to the private sector, through the separation of the financing and the provision. The result is the creation of a new institutional scheme of the Lombard health system, which can be recognised by its own layout.